Analysis of liquefaction potential in Lolu Village, Palu using SPT method and laboratory test of grain size distribution. Issue 1 (January 2021) - Rahayu, W; Nurizkatilah; Bahsan, E
Abstract: Liquefaction is known to be a natural phenomenon where granular soil material from its solid to liquid form. One of its impacts is from an earthquake that occurred in Palu in September 2018. This research will conduct an analysis based on field test data of Standard Penetration Test (SPT) and laboratory test data of Grain Size Distribution. Samples were taken from five different boreholes. The analysis will use the Idriss and Boulanger method, referring to the soil safety factor's value to evaluate the liquefaction potential. For grain size analysis, evaluation of liquefaction potential is carried out referencing liquefaction based on grain grading of Tsuchida, the coefficient of uniformity, and the curvature of the liquefied soil. The results showed that liquefaction potential was found from 1 m depth to 20 m with N-SPT value ranging from 3 – 54 blows. On the other hand, analysis using a grain distribution test showed that soil at the location is dominated by sandy soil with fine-grained contents that can experience liquefaction.